APLIKASI GAME Si PITUNG “HAWKEYE DARI INDONESIA“ BERBASIS ANDROID - Muhammad, Adianzah; Tri Handoko, Widiyanto (Information Technology and Telematics, 2018)
Abstract Folklore is an spoken tradition that generally decreases inherited in people's lives. Folklore is usually in the form of speech that functions as a medium for the disclosure of behavior about the values of life inherent in people's lives. Examples of folklore, Pitung. The development of today's technology makes the community, especially children began to forget and choose to play games through smartphones. Therefore, this study aims to find out how to make the Si Pitung game application "Hawkeye from Indonesia" based on android with a design that is easy to use and can function as an educational medium. The method of making this game is collision detection starting from the analysis of design, manufacture, testing and maintenance. The game model presented in the form of pitung characters as the main character, and there are 3 levels of adventure genre. Each level has a mini-game in the form of multiple choices and guess images that contain pitung folklore and betawi culture. The results showed that the game Si Pitung "Hawkeye from Indonesia" Based on Android made using construct 2 can be run on a mobile device with an Android platform easily by users. So that it can help children to get to know Si Pitung folklore and Betawi culture